Optimizing Flammulina velutipes residue use: impact on health metrics and performance in three-yellow chickens - Li, Yuanxiao; Liu, Dan; Li, Wang; Zhao, Longmei; Cao, Pinghua; Ma, Yanbo; Ding, Ke; Zhang, Cai; Liu, Ning (Frontiers in Animal Science, 2025)
IntroductionThis study investigated the effects of Flammulina velutipes residue (FVR) on performance, antioxidant function, immunity, and intestinal flora of broilers.MethodsA total of 192 one-day-old three-yellow chickens were divided into four groups of 48 chickens per group, 6 replicates per group and 8 chickens per replicate. The control group (CON) was fed a basal diet, while the remaining three groups were supplemented with FVR in the basal diet, adding 2%, 4% and 6% of the basal diet, respectively. The experiment lasted for 48 days. Blood samples were collected from the jugular vein on days 28 and 48 to determine serum biochemical indices. Caecum contents were collected on day 48 to assess flora diversity.Results and discussionNo significant differences were observed in dry matter intake (DMI), average daily gain (ADG), or feed conversion ratio (FCR) between the 2% and 4% group and the CON. However, the 6% FRV group showed significantly reduced DMI and FCR. The FVR groups exhibited significantly increased levels of catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPC-PX) and total antioxidant capacity (T-AOC), along with significantly decreased malondialdehyde (MDA) content. Additionally, serum interleukin-1 (IL-1) levels decreased, while immunoglobulin G (IgG), immunoglobulin A (IgA) and interleukin 10 (IL-10) levels significantly increased in the FVR groups. The caecal flora diversity test revealed that FVR altered the flora structure, with increased proportions of Bacteroides, Ruminococcus and Faecalibacterium in the 6% FVR groups. In conclusion, FVR can significantly enhance the antioxidant capacity and immunity of broilers and enrich the structure of intestinal flora. The impact on growth performance is limited and dosage-dependent. Further research is needed to optimize its use in poultry diets.